MICROBIOLOGICAL ANALYSIS OF PERIODONTAL PATHOGENS USING THE BANA TEST TO DIABETES MELLITUS PATIENTS - Imelda Ramona Dinu; Marius Andrei Dinu; Anca Dumitriu; Horia Traian Dumitriu (Romanian Society of Oral Rehabilitation, 2014)
The aim of study was to evaluate the periodontal condition of 15 non-diabetic patients (age range, 30-77 years) compared to 15 patients without diabetes. The BANA (N-benzoyl-DL-arginine-naphthylamide) test was used to analyze subgingival microbiota.The diabetic group was subdivided into three groups according to the degree of diabetic control: controlled, moderately controlled and poorly controlled. When the diabetic patients were subdivided and compared to the control group, significance was detected (P<0.01) in the total frequencies of the BANA scores (negative, moderately positive and positive: 1, 2, and 3, respectively) in the 5, 6-, and 7 mm pockets and also in the 4 mm pockets in the controlled group.